INTERVENSI ULTRASOUND DAN PERTURBATION EXERCISE LEBIH EFEKTIF DARIPADA ULTRASOUND DAN MOBILIZATION WITH MOVEMENT UNTUK MENINGKATAN KEMAMPUAN FUNGSIONAL PADA PENDERITA OSTEOARTHRITIS GENU - Pramana Putra, I Putu Yudi; Sutjana, Dewa Putu; -, Wahyuddin; Tirtayasa, Ketut; Ratna Sundari, Luh Putu; Irfan, Muh. (Sport and Fitness Journal; Volume 7, No.1, Januari 2019DO - 10.24843/spj.2019.v07.i01.p09, 2019)
ABSTRACT Background: Osteoarthritis is some of problem on joint which have a function for supporting body and have chronic and degenerative characteristic so it can affects the cartilaginous structure of joint it can cause some of abnormality of bones, soft tissues, and synovial fluid like pain, decrease on range of motion (ROM), deformity and morning stiffness which is most often felt especially in knee joint. Purpose: This study was to determine affectivity combination intervention of ultrasound and perturbation exercise with ultrasound and mobilization with movement to improve functional ability for people with osteoarthritis genu. Methods: This research used experimental method with pre and post test control group design. Subject of this research are 22 people and divided into two groups where on the group 1 was given intervention of ultrasound and perturbation exercise and group 2 was given intervention of ultrasound and mobilization with movement with intensity 2 times per week for 12 times total intervention. Measurement functional score ability improvement was measured using a WOMAC index. Result: Group 1 result obtained p value = 0.001 (p <0.05) and in Group 2 got result obtained p value = 0.001 (p<0.05) for Paired Sample T-test. Different test of mean value with independent sample t-test after treatment found that the increase of improve functional 21.45±4.132 in group 1 and 11.55±1.368 in group 2 with p value = 0.036 (p <0.05). Conclusion: Intervention of ultrasound and perturbation exercise is significantly more effective compared with ultrasound and mobilization with movement for improve functional ability for people with osteoarthritis genu. Suggestion: For the next researcher can do follow up research to see long-term result intervention of ultrasound, perturbation and mobilization with movement for improve functional ability for people with osteoarthritis genu. Key Word; Osteoarthritis genu, perturbation exercise, mobilization with movement, ultrasound, WOMAC